Charter of the City of New Haven 142-43 (1881) - (:unkn) unknown (My University, 1881)
§ 18: Prohibited the sale of any fixed ammunition, gun, pistol, or other mechanical contrivance arranged for the explosion of cartridge, or any fulminate to any child under the age of sixteen.
Keywords: TRANSFER - MINORS